UJARAN KEBENCIAN DALAM KOLOM KOMENTAR INSTAGRAM @kaesangP: ANALISIS LINGUISTIK FORENSIK - Pardosi, Santa Rosa (STKIP PGRI SUMENEP, 2025)
This article discusses hate speech in the Instagram comments section of a businessman who is currently in politics using forensic linguistic analysis. The purpose of this study is (1) analysis of the type of hate speech contained in the @kaesangp comment column, (2) analysis of the lingual unit of disclosure of the type of hate speech in the @kaesangp Instagram comment column. This type of research is qualitative research with descriptive methods. The results of this study show that the types of hate speech in the Instagram comment column of political figures found in this study consist of provocation, incitement, insults, blasphemy, defamation, and fake news. Speech acts found in all types of hate speech consist of locution, illocution, and perlocution. Then, the lingual unit of hate speech disclosure in the comment column @kaesangp consists of words, sentences, phrases in the form of: noun phrases, phrases, verb phrases, adverb phrases, and adjectival phrases.